Efforts to Improve Knowledge, Attitudes and Behaviors about Dental and Oral Health Through the Use of TikTok App for Pregnant Women - Fratiwi, Winda; Kristiani, Anie; Anang, Anang (Journal Center of Excellent : Health Assistive Technology, 2024)
Background: Pregnancy is one of the factors that can cause an increase in dental and oral health problems. This condition occurs due to increased levels of the hormones estrogen and progesterone during pregnancy, which is associated with an increase in the amount of plaque attached to the surface of the teeth and oral hygiene which tends to be neglected due to nausea and vomiting in the morning (morning sickness), especially in the early stages of pregnancy. Providing counseling by utilizing TikTok can be an effective way for pregnant women to increase knowledge, attitudes and behaviors about dental and oral health. Research: The purpose of this research is to create and develop dental health promotion by using the Tiktok App to increase knowledge, attitudes and behaviors about dental and oral health in pregnant women at the posyandu Village in the Mangkubumi Health Center area. Research: The type of research conducted was R&D research. Research: Tiktok App about dental and oral health can improve the knowledge, attitudes and behaviors of pregnant women. P value of knowledge 0.000, attitude 0.000 and behavior 0.000. Conclussion: Dental health promotion using the Tiktok App can increase knowledge, attitudes and behaviors about dental and oral health in pregnant women at the posyandu Village in the Mangkubumi Health Center area